2021
DOI: 10.3390/math9060627
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Damaged Rotor Blades on the Aerodynamic Behavior and Heat-Transfer Characteristics of High-Pressure Gas Turbines

Abstract: Gas turbines are critical components of combined-cycle power plants because they influence the power output and overall efficiency. However, gas-turbine blades are susceptible to damage when operated under high-pressure, high-temperature conditions. This reduces gas-turbine performance and increases the probability of power-plant failure. This study compares the effects of rotor-blade damage at different locations on their aerodynamic behavior and heat-transfer properties. To this end, we considered five cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Comparisons of kinetic energy and shear stress were reported as well. (Mai and Ryu, 2021) compared the effects of rotor-blade damage at different locations in the LE-SS, and LE-PS regions on their aerodynamic behavior and heat-transfer using the CFD approach. Their results reported that damaged-blade cases revealed an increase in the aerodynamic force acting on the blade/vane surfaces.…”
Section: Numerical Investigation Of Effects Of Damaged and Repaired S...mentioning
confidence: 99%
“…Comparisons of kinetic energy and shear stress were reported as well. (Mai and Ryu, 2021) compared the effects of rotor-blade damage at different locations in the LE-SS, and LE-PS regions on their aerodynamic behavior and heat-transfer using the CFD approach. Their results reported that damaged-blade cases revealed an increase in the aerodynamic force acting on the blade/vane surfaces.…”
Section: Numerical Investigation Of Effects Of Damaged and Repaired S...mentioning
confidence: 99%
“…In this study, the governing equation is the URANS equation, as shown in Equations ( 3) and ( 4) [23,24], and the turbulence model SST k-ω [25,26] was applied to enclose the equation.…”
Section: Boundary Condition and Governing Equationmentioning
confidence: 99%
“…In addition, several studies employed computational fluid dynamics (CFD) to evaluate the internal characteristics and performance of gas turbines in various applications. Mai and Ryu 10,11 estimated the aerodynamics and heat-transfer effects of a damaged blade in a 1.5-stage high-pressure gas turbine. Nguyen et al 12 conducted a single-stage high-pressure gas turbine simulation to compare the effects of chemical reactions on the flow parameters.…”
Section: Introductionmentioning
confidence: 99%